Using digital twins to create an inventory management system - Kukartsev Vladislav; Kozlova Anastasia; Kuimova Olga; Nelyub Vladimir; Gantimurov Andrei (E3S Web of Conferences, 2023)
The article considers the application of the inventory management model on the example of a manufacturing enterprise, where it is planned to use a digital twin together with the inventory management system. Inventory management model is a mathematical model that allows you to determine the optimal level of stocks at the enterprise. In a manufacturing enterprise, this model can help optimize the inventory of raw materials, materials, and finished goods, which will reduce costs and reduce risks associated with the lack of necessary raw materials or required quantities of finished goods. With the help of data obtained from the enterprise, the input parameters of the model were obtained, namely the size of resource consumption, stock holding costs, delivery realization costs, and time required for delivery. The model was used to find the parameters such as optimal order size, delivery period, inventory level at which ordering should be carried out.